The sterling public servant : a global tribute to Sylvia Ostry - Ostry, Sylvia, 1927-; Ryten, Jacob (Published for the Canadian Institute of International Affairs by McGill-Queen's University Press, 2004)
In order to mark Sylvia Ostry's seventy-fifth birthday, a group of some twenty of her friends and professional colleagues were invited to provide papers closely related to her work. Among the contributors are other national representatives at the G-7 Economic Summit who overlapped with her term of service, academics with whom she collaborated or broke friendly lances during her scholarly career, and fellow senior civil servants who were colleagues and counterparts during her years of service. Sylvia Ostry: A Global Tribute marks a milestone in her career and reflects the relevance and importance of her contributions. It includes congratulatory letters from all living prime ministers.